The Creation and Destruction of The Universe: Comparison of The Perspectives in Science and The Qur’an - Teuku Muhammad Hary Ramadhan; Mustanir Yahya; Safrida S; Sulastri Sulastri; A Halim (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2023)
Abstract: This paper aims to analyze the comparison of the concepts of creation and destruction of the universe from the perspective of science and the Qur'an, by analyzing some relevant literature. The majority of the literature used in this paper comes from the ScienceDirect database. The keywords used in the reference search were